Pibid and Residência: teaching practices in History/Fafidam/Uece - Ulisses, Ivaneide Barbosa (2022)
The proposal was to discuss interactions, dialogues in practices between Pibid (Program Institucional de Bolsa de Iniciação à Docência) and PRP (Programa Institucional de Residência Pedagógica) with teaching subjects, in the History course of FAFIDAM/UECE. The programs aim to provide students approximations with the daily life of public schools of basic education, inserted by knowledge and experiences with academic training, in order to contribute to the training of these students. The subjects have as common proposals to analyze the different aspects of teaching action as a professional practice based on historically constructed knowledge and to reflect on the teaching-learning process in History, in the other words, to think and perform teaching based on the relationship of teaching and reaserching in Historical Science.